Spirit(s), Angels, and Virtues: The Reception of Isaiah 11:2–3a in Early Judaism - Johansson, Simon (Verbum Vitae, 2025)
This article examines the reception history of Isa 11:2–3a in Second Temple Judaism, as it relates to pneumatological perceptions and uses of the words for “spirit” in Hebrew and Greek (rûaḥ and pneuma). Isaiah 11 plays an important role in messianic expectations in both Judaism and Christianity, but its reception in early Judaism sheds light also on early pneumatological developments and forms the background to later, early Christian interpretations of this text. Via close readings and analyses of (1) The Septuagint translation of Isa 11:2–3a; and relevant texts from (2) Qumran; (3) the Jewish Apocrypha and Pseudepigrapha; and (4) the Targum Isaiah this study demonstrates different interpretative lines and uses of “spirit.” The main conclusions are that there are both royal or messianic and more “democratized” interpretations and applications of the original “royal charisma” in Isa 11:2; furthermore, that “spirit” can be used to denote the spirit of God, human dispositions, charismatic gifts or virtues, and angelic beings—and, sometimes, the distinctions between these categories are blurry and overlap.